Reviews of accelerator science and technology. - Chao, Alexander Wu; Chou, Weiren (World Scientific, 2011)
Over the last half century we have witnessed tremendous progress in the production of high-quality photons by electrons in accelerators. This dramatic evolution has seen four generations of accelerators as photon sources. The 1st generation used the electron storage rings built primarily for high-energy physics experiments, and the synchrotron radiation from the bending magnets was used parasitically. The 2nd generation involved rings dedicated to synchrotron radiation applications, with the radiation again from the bending magnets. The 3rd generation, currently the workhorse of these photon s.